Misyari Rasyid Alafasyi’s “Qolbi Muhammad” Song Lyrics: Michael Riffaterre’s Semiotic Study - Dihyat Haniful Fawad; Muassomah Muassomah; Helmi Syaifuddin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The purpose of this study is not only to reveal the heuristic meaning in the lyrics of the song